α-Linolenic Acid Suppresses Proliferation and Invasion in Osteosarcoma Cells via Inhibiting Fatty Acid Synthase - Huijin Fan; Wenyuan Huang; Yong Guo; Xiaofeng Ma; Jianhong Yang (Molecules, 2022)
Fatty acid synthase (FASN) is highly expressed in multiple types of human cancers and is recognized as one of the targets for treating cancer metastasis. α-Linolenic acid is an omega-3 essential fatty acid and it possesses various biological activities. The present study was designed to reveal the effects of α-linolenic acid on osteosarcoma and to reveal whether the mechanism of α-linolenic acid in anticancer activity may be related to FASN inhibition. The cytotoxicity of α-linolenic acid was assessed in osteosarcoma MG63, 143B, and U2OS cells. Cell viability was detected by the MTT assay. The protein expression level was detected by western blotting. Flow cytometry, Annexin V/propidium iodide dual staining, and Hoechst 33258 staining were performed to assess the apoptotic effects. Wound healing assay was applied to detect the inhibitory effect of α-linolenic acid on osteosarcoma cells migration. The results showed that α-linolenic acid downregulated FASN expression. α-Linolenic acid inhibited osteosarcoma cell proliferation and migration in a dose-dependent manner. In addition, α-linolenic acid regulated endoplasmic reticulum transmembrane receptors and signal protein expression in osteosarcoma cells. The findings of the present study suggested that α-linolenic acid suppresses osteosarcoma cell proliferation and metastasis by inhibiting FASN expression, which provides a basis as a potential target for osteosarcoma treatment.